2020
DOI: 10.1177/0300060520974465
|View full text |Cite
|
Sign up to set email alerts
|

Sjögren’s syndrome with rapidly progressive motor neuron disease: a case report

Abstract: Sjögren’s syndrome is an autoimmune disease that can affect multiple systems. Sjögren’s syndrome with motor neuron disease is rarely reported. Herein, we describe a patient with rapidly progressive motor neuron disease secondary to Sjögren’s syndrome. A 42-year-old woman was admitted to our hospital with a 2-month history of progressive limb weakness. Neurological assessment revealed fasciculation in the lower limbs and amyotrophy in the bilateral supraspinatus, interosseous, and thenar muscles. Serological ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
1
0
4
Order By: Relevance
“…Foi feito um rastreio a fim de buscar novos meios de conduta para tratamento, os artigos encontrados incluíam abordagem sintomática, tratamentos imunossupressores, como ciclofosfamida e hidroxicloroquina, uso de corticosteroides, como administração de metilprednisolona, e uso de imunoglobulina humana 9,[13][14][15][16][17] . A maioria dos relatos traziam a melhora ou recuperação neurológica significativa do paciente quase imediatamente após a terapia medicamentosa, diferentemente com o que observamos nesse caso.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Foi feito um rastreio a fim de buscar novos meios de conduta para tratamento, os artigos encontrados incluíam abordagem sintomática, tratamentos imunossupressores, como ciclofosfamida e hidroxicloroquina, uso de corticosteroides, como administração de metilprednisolona, e uso de imunoglobulina humana 9,[13][14][15][16][17] . A maioria dos relatos traziam a melhora ou recuperação neurológica significativa do paciente quase imediatamente após a terapia medicamentosa, diferentemente com o que observamos nesse caso.…”
Section: Discussionunclassified
“…A paciente evoluiu com insuficiência respiratória, e veio a óbito. Esse caso nos preocupa por sua semelhança clínica com nossa paciente, melhor evidenciada no Quadro 1, que também cursa com piora progressiva sem resposta aparente a nenhum tratamento 9 .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Yang et al recently reported rapidly progressive motor neuron disease in a patient with Sjögren's syndrome. The patient did not respond to treatment and died [ 21 ]. In a study reported by Seeliger et al, 184 patients with polyneuropathy associated with limb weakness were evaluated for Sjögren's syndrome (ACR-EULAR classification criteria), and Sjögren's syndrome was determined in 44 patients [ 38 ].…”
Section: Discussionmentioning
confidence: 99%